Pemenuhan Persyaratan Perubahan Status Desa Menjadi Kelurahan pada Desa Masintan Kecamatan Kelua Kabupaten Tabalong - Nuria Maulidah (Prodi PPKn ULM dan AP3KnI Kal-Sel, 2015)
Chage of status will berimplementasi on social and economic aspects that will economic aspects that will lead to the development of the village to a prosperous society and a prosperous.The administration of local government activities must always continue to rise as well as in rural districts Masintan so fa districtTabalong consequences for eligibility status in the village changes into village this study aims to determine the infrastructure and governance, economic potential held in impra aspect and superstructure village, social and cultural conditions, an increase in the volume of services in rural Masintan.The research method used was a qualitative research method. Data collection was done by using observation, interview and documentation. Analysis of the results of the research is the analysis of the data reducatoin step, the presentation of the data and drawing conclisions.The results of this study indicate that the infrastructure in the village of unmet Masintan both in terms of roads, bridges The potential economic views of the infrastructure has not qualified, because its people economically most prominently the agriculture, community nearly 85% of farmers, the rice farmers socio-cultural. Nearly fulfilled and volume of services also met. Based on the results of this study, it can be suggested to improve the facilities andInfrastructures are in desq Masintan. In order to meet it should be in coordination RT, RW, Community leaders in promoting a change in the village into the village and these proposals be implemented either at the district or county level.Keywords: socio-cultural changes in the economic infrastructure and the volume of services